Multi-hole spherical CT scan method to characterize large quantities of bones in rats (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND New therapeutic options are often explored in in vivo studies using animals like rats. Since rats are small, it is difficult to examine them in a computed tomography (CT) scan. This study aimed to introduce a multi-hole spherical model CT scan method as a new, fast, economical, and reliable method to characterize large quantities of rat bones at once in estimating the timing of osteoporosis in ovariectomized white rats. METHODS 50 female white rats (12 weeks old) were treated as the control group, and 40 rats of the same age were ovariectomized to establish the osteoporosis model. Sham rats were sacrificed at 13, 15, 17, 19, and 21 weeks old, while the ovariectomized rats were sacrificed at 15, 17, 19, and 21 weeks old. Afterward, tibia bones were removed, placed in the multi-hole spherical model, and characterized using a CT scan. Their characteristics were compared using a scanning electron microscope (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD). RESULTS The Hounsfield unit scores resulted from the multi-hole spherical model CT scan method of tibia bones of rats were consistent with the percentage of the osteocyte cavities, canalicular diameters, and crystal size. The multi-hole spherical model CT scan method could produce 50 times more data than the SEM, TEM, or XRD. CONCLUSIONS Multi-hole spherical model CT scan was considered good and reliable in assessing bone quality parameters in rat samples simultaneously.